2017
DOI: 10.1088/1361-6471/aa84da
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the decay rate of tachyonic neutrinos against charged-lepton-pair and neutrino-pair Cerenkov radiation

Abstract: We consider in detail the calculation of the decay rate of high-energy superluminal neutrinos against (charged) lepton pair Cerenkov radiation (LPCR), and neutrino pair Cerenkov radiation (NPCR), i.e., against the decay channels ν → ν e + e − and ν → ν ν ν. Under the hypothesis of a tachyonic nature of neutrinos, these decay channels put constraints on the lifetime of high-energy neutrinos for terrestrial experiments as well as on cosmic scales. For the oncoming neutrino, we use the Lorentz-covariant tachyonic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 63 publications
2
23
0
Order By: Relevance
“…The obtained results have been applied to the study of neutrino flavor oscillations. In particular, on the basis of recent experimental results concerning ultrarelativistic neutrinos up to energies of the order of the PeV scale [46], we propose a theory in which flavor changes occur through the creation of superluminal states, obtained by the interaction of a neutrino with the surrounding matter. This theory, although still speculative, might be verified by measuring the travel times of only high-energy neutrinos between a source and detector that arrive at the detector with a changed flavor.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained results have been applied to the study of neutrino flavor oscillations. In particular, on the basis of recent experimental results concerning ultrarelativistic neutrinos up to energies of the order of the PeV scale [46], we propose a theory in which flavor changes occur through the creation of superluminal states, obtained by the interaction of a neutrino with the surrounding matter. This theory, although still speculative, might be verified by measuring the travel times of only high-energy neutrinos between a source and detector that arrive at the detector with a changed flavor.…”
Section: Resultsmentioning
confidence: 99%
“…In Sec. 2.3 of [28], it has recently been shown that this is the case, for both tachyonic (Lorentz-conserving) as well as Lorentz-violating superluminal neutrinos, for surprisingly large incoming neutrino energies. Its range of applicability covers the entire kinematic regime from zero neutrino energy up to the "Big Bird" energy (Refs.…”
Section: A Theoretical Basis and Assumptionsmentioning
confidence: 96%
“…(7), according to v ≈ 1 + δ/2, we are consistent with Refs. [17,20,26,28], while Refs. [8,13,14] choose their δ parameters to be equal to just the difference v − 1.…”
Section: A Theoretical Basis and Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It ranges from the physics of high energies tested in particle accelerators [5,6] to astrophysics [7][8][9][10], passing through many new theories aiming to explain its anomalies [11,12]. Among these anomalies, that of superluminal neutrinos is the most debated, the publications dedicated to it only multiplying [13][14][15][16]. Recently, the controversy about the data of the OPERA experiment in 2011 raised questions about the abilities of neutrinos to travel faster than light.…”
Section: Introductionmentioning
confidence: 99%